2011
DOI: 10.18356/6487d1bb-en
|View full text |Cite
|
Sign up to set email alerts
|

Risk managmement networks of ethnic minorities in Viet Nam

Abstract: The utilization of informal social networks is an important risk management strategy of vulnerable households in SouthEast Asia. To gain insight on this issue, a social network analysis (SNA) was implemented to assess risk management networks of ethnic minority farm households in the northern uplands of Viet Nam. The results from the analysis suggest that kinship relations and the level of wealth play an essential role in enabling basic network services to function. This paper also points out that effective ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…Risk sharing network from ethnic minority people are more likely to be confined within village boundaries, making ethnic minorities highly vulnerable to aggregated shocks. This result confirms what Fischer et al (2010) find based on case studies of ethnic minority people in North Viet Nam. They show that the majority of help flows remain within the village.…”
Section: Determinants Of Geographic Similarity Within Risk Sharing Nesupporting
confidence: 91%
“…Risk sharing network from ethnic minority people are more likely to be confined within village boundaries, making ethnic minorities highly vulnerable to aggregated shocks. This result confirms what Fischer et al (2010) find based on case studies of ethnic minority people in North Viet Nam. They show that the majority of help flows remain within the village.…”
Section: Determinants Of Geographic Similarity Within Risk Sharing Nesupporting
confidence: 91%
“…The community role refers to women's activities within the community, maintaining social networks and relations as well as the provision of items for collective consumption such as contributions to religious festivals (Moser 1993). The community role is often overseen and not recognized even though it is a fundamental part of the household's security and risk-management net (Beuchelt 2008;Fischer et al 2010). …”
Section: Potential Trade-offs Of Agricultural Technologies From a Genmentioning
confidence: 99%
“…Whether for accessing different types of assets or financial capital, for mobilizing the labor force needed to implement adaptation actions, or for getting information to access credit or grants, the networks of interpersonal relationships involving kinship, lineage, neighborhood, friendship, and clientelism can lever material and immaterial support for their members. In concrete terms, the local informal loan system, local rotating savings and credit groups, informal safety nets, as well as labor exchange practices, land arrangements, and the intense flow of gifts and mutual services allow people to access a wide range of resources directly mobilized to cope with and adapt to climate change [2,3,10,30,[43][44][45]. We present in the Box 1 a case study conducted in Northern Vietnam's upland area, dealing with the responses and adaptation to weather-related disaster, to show a manifestation of these social dynamics that shape adaptation finance in rural Vietnam.…”
Section: The Use Of Adaptation Funding and Its Drivers At The Communementioning
confidence: 99%
“…At the local level, in addition to the government support, communities have tried their best to mobilize resources for dealing with sudden climate related hazards. Many studies have shown for a long time already how different categories of households tend to use their own available resources to adapt to climate variability [2][3][4][5]. Despite this variety of financing sources, it seems that funds for adaptation actions at the national level may be connected with difficulty to local adaptation needs.…”
Section: Introductionmentioning
confidence: 99%